Evaluation of an integrated lighting-warning system on motorists' yielding at unsignalized crosswalks during nighttime. (January 2020) - Costa, Marco; Lantieri, Claudio; Vignali, Valeria; Ghasemi, Navid; Simone, Andrea
Highlights: Driver's yielding to pedestrian at nighttime double when enhanced lighting is active. In-curb LED lighting strips could alert driver's attention to pedestrians. In-curb flashing LED strips and flashing beacons increase motorists' yielding. An integrated lighting-warning system could strongly increase yielding compliance. Abstract: Drivers' yielding behavior to pedestrians during nighttime was assessed in seven different conditions of crosswalk lighting: (a) baseline condition with standard road lighting; (b) enhanced LED lighting that increased lighting level from 70 to 120 lx; (c) flashing orange beacons on top of the backlit pedestrian crossing sign; (d) in-curb LED strips on the curbsides of the zebra crossing with steady light emission; (e) in-curb LED strips with flashing light emission; (d) all previous devices activated with in-curb LED strips in steady mode; (e) all previous devices activated with in-curb LED strips in flashing mode. For every condition 100 trials were recorded with a staged pedestrian that initiated a standardized crossing when a vehicle was approaching. The frequency of drivers' yielding was computed for each condition. A significant increase for yielding compliance was recorded from standard road lighting to enhanced dedicated lighting (19–38.21%), and from enhanced dedicated lighting to the seventh condition with the flashing beacons and the flashing in-curb LED strips activated (38.21–63.56%). The results showed that the integrated lighting-warning system for pedestrian crossings was effective in increasing motorists' yielding to pedestrians during nighttime.